ADAPTIVE REUSE PADA GEDUNG PERTUNJUKAN DE MAJESTIC SEBAGAI BANGUNAN CAGAR BUDAYA GOLONGAN A DI KOTA BANDUNG - Victoryana, Jessica; Dibyo Hartono, Harastoeti (Jurnal Riset Arsitektur, 2023)
Abstract - De Majestic Performing Art Building is a cultural heritage building type A in the Bandung City. The building that is located at Braga Street 1, Bandung was built in the early 1920 with the original labelled as Concordia Bioscoop. De Majestic was the first cinema that is established in the Bandung City and was the first cinema that show the first film in the city. Unfortunately, the heyday of De Majestic Building only lasted until the year of 2002, where conservation and replacement of the function were carried out. Throughout its age, this building has undergone several conservation efforts along with the times, as well as changes in the management. The changes that have been done including; Gedung Bioskop Majestic, Asia Africa Cultural Center, New Majestic, Gedung Pertunjukan De Majestic. This building also has a fairly dark history that occurred in 2008, this has caused a lot decrease in public interest in visiting and using this building. With this condition, the building has received less attention as a cultural heritage building in the city of Bandung, even though the physical condition of the building itself can be categorized as well-maintained and can still be optimized. Therefore, this research leads to an evaluation of De Majestic Building of its function in order to recreate a worthwhile study to increase the vitality and maximize the potential of the building. This study uses descriptive methods and qualitative evaluation, by examining the physical and operational conditions of De Majestic Building. After those, an analysis is also applied regarding the alignment of the area where the building stands, and the allocation of the area in accordance with the Bandung City regulations that have been set by the government. This research also refers to theories related to building conservation, principles of adaptive reuse process, regulations governing cultural heritage buildings in Indonesia. The result of this research is an idea and a new function idea that has gone through the analysis process which means it has the greatest potential to be implemented in the De Majestic Building. The selected new function idea have gone through analysis such as the define of its location, historical value, building characteristics, space requirements, and the potential of the building for the area. The existence of a new function is expected to increase the vitality of the building and interest in visiting buildings and areas, as well as restore values that have begun to fade in this modern era among the community. With the new function ideas, local and non-local people can participate in maintaining, protecting, and utilizing the existence of Cultural Heritage Buildings in the Bandung City. Keywords: Conservation, Cultural Heritage Building, Adaptive Re-Use, De Majestic Bandung